A Detailed description of Rugarhynchos sixmilensis, gen. et comb. nov. (Archosauriformes, Proterochampsia), and cranial convergence in snout elongation across stem and crown archosaurs. Issue 6 (2nd November 2019) - Wynd, Brenen M.; Nesbitt, Sterling J.; Stocker, Michelle R.; Heckert, Andrew B.
ABSTRACT: The Triassic Period (252–201.5 Ma) records a great expansion of saurian diversity and disparity, particularly in skull morphology. Stem archosaurs exhibit substantial cranial disparity, especially by taxa either shortening or elongating the skull. This disparity is exemplified in the North American Late Triassic proterochampsians by the 'short-faced' Vancleavea and the 'long-faced' doswelliids. To critically investigate skull elongation and character evolution in these proterochampsians, we evaluate ' Doswellia ' sixmilensis, known from much of a skull, cervical centra, and osteoderms from the Bluewater Creek Member of the Chinle Formation of New Mexico. We redescribe the holotype based on extensive repreparation of the holotype material, resulting in the identification of the orbit and clarifying the extent of related bones. As such, the diagnosis of the taxon is substantially modified and a new genus, Rugarhynchos, gen. nov., is erected. Rugarhynchos sixmilensis, gen. et comb. nov., exhibits an elongate snout with characteristics known in stem and crown archosaurs, including a downturned premaxilla and fluted teeth. We included R. sixmilensis in a phylogenetic analysis of archosauromorphs consisting of 677 characters and 109 taxa under both parsimony and Bayesian models. We recover R. sixmilensis as a doswelliid, sister to Doswellia kaltenbachi . Our parsimony and Bayesian models differ in the placement of Doswelliidae, either as sister to or within Proterochampsidae, respectively. We use archosauromorph relationships from the Bayesian model to estimate cranial disparity between stem and crown archosaurs and find a narrow breadth of morphological disparity in the stem. Our results suggest that crown archosaurs evolved disparate crania from a low-disparate archosauriform condition.